Lactate: a rising star in tumors and inflammation - Liu, Hui; Pan, Mengmeng; Liu, Mengxia; Zeng, Lin; Li, Yumeng; Huang, Zhen; Guo, Chunlei; Wang, Hui (Frontiers in Immunology, 2024)
Lactate has been traditionally regarded as a mere byproduct of glycolysis or metabolic waste. However, an increasing body of literature suggests its critical role in regulating various physiological and pathological processes. Lactate is generally associated with hypoxia, inflammation, viral infections, and tumors. It performs complex physiological roles by activating monocarboxylate transporter (MCT) or the G protein-coupled receptor GPR81 across the cell membrane. Lactate exerts immunosuppressive effects by regulating the functions of various immune cells (such as natural killer cells, T cells, dendritic cells, and monocytes) and its role in macrophage polarization and myeloid-derived suppressor cell (MDSC) differentiation in the tumor microenvironment. Lactic acid has also recently been found to increase the density of CD8+ T cells, thereby enhancing the antitumor immune response. Acute or chronic inflammatory diseases have opposite immune states in the inflammatory disease microenvironment. Factors such as cell types, transcriptional regulators, ionic mediators, and the microenvironment all contribute to the diverse functions lactate exhibits. Herein, we reviewed the pleiotropic effects of lactate on the regulation of various functions of immune cells in the tumor microenvironment and under inflammatory conditions, which may help to provide new insights and potential targets for the diagnosis and treatment of inflammatory diseases and malignancies.